Power semiconductors - Linder, Stefan, 1965- (Lausanne, Switzerland : EPFL Press ; Boca Raton, FL : Distributed by CRC Press, 2006)
The aim of this book is to provide an overview of the various types of power semiconductor devices, to give an insight into how they function, and to explain and analyze the characteristics of the various components. All the important classes of power semiconductors are covered. Of particular interest, the author takes into account the role of plasma formation in the operation of highpower semiconductor devices.
Fundamentals of semiconductor physics -- The p-n Junction -- The Pin Diode -- The Bipolar Transistor -- The Thyristor -- The GTO and GTC / IGTC -- The Power MOSFET -- The IGBT -- List of symbols -- Constants -- Units -- Unit prefixes -- Writing conventions -- Circuit symbols in electrical engineering -- Material properties at 300 K.
Includes bibliographical references and index.
Keywords: Power semiconductors; Thyristors; Metal oxide semiconductor field-effect transistors; Insulated gate bipolar transistors